PERBANKAN DAN INDIKATOR EKONOMI : SEBUAH ANALISA KETIMPANGAN DISTRIBUSI PENDAPATAN DI ASEAN-3 - Rulita, Insyira; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2023)
This study aims to find the factors influencing economic growth and income inequality in ASEAN-3 countries from 1990-2019. The research method used in this study was a quantitative research method using Two Stages Least Square analysis. The results of this study indicate that the credit variable has a positive and significant effect in Indonesia but has a significant negative impact in Thailand and Singapore on economic growth. In contrast, the inflation variable has a negative and significant impact on economic growth but has a positive and significant effect in Thailand and Singapore. The savings variable does not significantly affect economic growth in Indonesia, Thailand, and Singapore. Furthermore, the economic growth variable has a positive and significant effect on income inequality in Indonesia and Thailand but has a negative and significant impact on Singapore.